Forests Fanned by Waves: Embodied Ways of Knowing in a Mangrove Landscape - Kalyanasundaram, Sandhiya (The Trumpeter, 2022)
This narrative article explores a boatman's intimate relationship with the mangrove forests he had grown up with from his childhood. The author listens to the boatman's stories about his life when he is in his sixties. How he assessed the author also implied what part of his world the author would be invited to see. This is a narrative of warmth and friendship built through traversing the mangrove forest in a handmade raft, watching birdlife, lotuses and other mangrove species. The narrative captures the ecosophy of this boatman in his lived and embodied experience.